UMP launches English bulletin, promotes Pekan name - UMP, PNC
In conjunction with Universiti Malaysia Pahang’s (UMP) Cendekia Bitara Award night, the university did a soft launch of its first English Bulletin – Pekan Review – at the Bukit Gambang Resort City on May 3.